The legitimacy of restricting the application of the provisions on free of charge the transfer of items made pursuant to art. 232b of the Code of Criminal Procedure - Łozińska-Piekarska, Agnieszka (Studia Iuridica Toruniensia, 2021)
The article discusses the free transfer of items of importance to health and public life, introduced to the provisions of the Code of Criminal Procedure, in connection with combating COVID-19. It presents in detail the conditions that must be met in order to use the procedure indicated in the provision of Art. 232b of the Code of Criminal Procedure, and it was also proposed to clarify it. The main demands were to limit the entities issuing the decision on the free transfer of items to judicial authorities, to clarify the list of entities to which these items can be transferred, as well as the list of items that should be classified as significant for health and public life. Another postulate is the introduction of the rules of suspending the execution of the decision on free handover of items until the complaint is examined, as well as the introduction of a quick procedure for obtaining compensation in case of infringement of the ownership right.